Pseudogene RPL32P3 regulates the blood–tumor barrier permeability via the YBX2/HNF4G axis - Ye Ding (Nature Publishing Group, 2021)
Abstract The existence of the blood–tumor barrier (BTB) severely hinders the transport of anti-tumor drugs to brain tumor tissues. Selectively opening BTB is of great significance to improve the chemotherapy effect of glioma. Pseudogenes have been recognized as important regulators in various biologic processes. In this study, we identified that ribosomal protein L32 pseudogene 3 (RPL32P3) was highly expressed in glioma-exposed endothelial cells (GECs). Knockdown of RPL32P3 decreased the expression of tight junction-related proteins (TJPs) and increased BTB permeability. Subsequent analysis of the underlying mechanism indicated that RPL32P3 recruited lysine methyltransferase 2 A (KMT2A) to the Y-box binding protein 2 (YBX2) promoter region and mediated H3K4me3 to promote YBX2 transcription. Highly expressed YBX2 bound and stabilized hepatocyte nuclear factor 4 gamma (HNF4G) mRNA. Highly expressed HNF4G directly bound to the promoters of TJPs ZO-1, occludin and claudin-5 to promote their transcriptional activities and regulated BTB permeability. The simultaneous knockdown of RPL32P3, YBX2, and HNF4G combined with doxorubicin (DOX) increased the apoptosis of glioma cells. In conclusion, the current study indicated that RPL32P3 knockdown increased BTB permeability through the YBX2/HNF4G pathway. These findings may provide new targets for the comprehensive treatment of glioma.